PERAN KOMUNITAS RACIKA PALM DALAM PENGELOLAAN SUMBER DAYA AIR BERKELANJUTAN DI KABUPATEN BATANG - Nugraha, Mustofa Fajar; Ajeng Mega Indriyani, Retno; Januar Hidayat, Reza (Bapelitbang Kabupaten Batang, 2025)
Human activities are causing global environmental changes that affect climate and water quality. Although water is crucial for life and the economy, previous management practices have not been sustainable. With increasing water demand and limited availability, new approaches to water resource management are needed for a sustainable future. Water resource management practices in Indonesia face challenges from social subsystems related to community participation in water resource management. This study employs a qualitative descriptive method supported by a Narrative Literature Review (NLR). Community participation in the Integrated Water Resources Management (IWRM) process has been emphasized by national regulations and researchers. The